2022
DOI: 10.1038/s41467-021-27193-9
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic nanoparticles that kill bacteria while sparing mammalian cells reveal the antibiotic role of nanostructures

Abstract: To dissect the antibiotic role of nanostructures from chemical moieties belligerent to both bacterial and mammalian cells, here we show the antimicrobial activity and cytotoxicity of nanoparticle-pinched polymer brushes (NPPBs) consisting of chemically inert silica nanospheres of systematically varied diameters covalently grafted with hydrophilic polymer brushes that are non-toxic and non-bactericidal. Assembly of the hydrophilic polymers into nanostructured NPPBs doesn’t alter their amicability with mammalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 70 publications
1
56
0
Order By: Relevance
“…Currently nanoparticles are tested in various fields such as catalysis [ 16 , 17 ], energy storage [ 18 ], energy conversion [ 19 , 20 ], and optoelectronic, for example, as light-emitting diodes [ 21 ]. In the case of the biomedical applications, NPs are tested not only as anticancer agents, which will be discussed later in this paper but also as antibacterial agents (for example in form of the layers on medical implants) [ 22 , 23 ], and sensitive tests to detect various diseases [ 24 , 25 ]. Generally, this wide application range is related to their unique properties and highly reactive surface.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Currently nanoparticles are tested in various fields such as catalysis [ 16 , 17 ], energy storage [ 18 ], energy conversion [ 19 , 20 ], and optoelectronic, for example, as light-emitting diodes [ 21 ]. In the case of the biomedical applications, NPs are tested not only as anticancer agents, which will be discussed later in this paper but also as antibacterial agents (for example in form of the layers on medical implants) [ 22 , 23 ], and sensitive tests to detect various diseases [ 24 , 25 ]. Generally, this wide application range is related to their unique properties and highly reactive surface.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Consistent with these microscopy observations, flow cytometry analysis, which utilized Annexin V and propidium iodide to quantitate apoptosis and necrosis, showed that the percentage of apoptotic/necrotic cells increased from 1.3% in the saline control group to 24.1% in cells treated with 0.0625 mg/mL NPCs plus NIR irradiation (Figure 3b). Despite the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay is prone to multiple interferences, including metal-based nanoparticles, this method has long been regarded as the gold standard for cell viability and proliferation studies, and thus been applied extensively in studies of metal-containing nanoparticles [18][19][20]. In accordance with our flow cytometry findings, the MTT viability assay showed that in combination with NIR irradiation, Fe 3 O 4 NPCs led to significant cell death in a dosage-dependent manner, with the efficacious concentrations starting at as low as 0.0625 mg/mL (Figure 3c).…”
Section: Photothermal Ablation Of Tumor Cells In Vitromentioning
confidence: 99%
“…The excited PDT is effective against a broad spectrum of bacteria strains, including the booming resistant bacteria, without developing any antimicrobial resistances. [14] Second, the PL emission of mPL NPs could effectively avoid the continuous use of external irradiations and alleviate autofluorescence interference from the tissues, performing much higher signal-to-noise ratios than traditional optical probes such as quantum dots and dyes. [42] Last but not least, the afterglow emission is used as an internal light source to persistently excite photosensitizers and generate ROS, which could overcome the short half-life and durability of traditional PDT.…”
Section: In Vivo Treatment Safety Of Mpl@pc-cy/lightmentioning
confidence: 99%
“…Bacterial membranes could be disrupted by metal ions, antimicrobial peptides, and cationic polymers, but these agents show unacceptable systemic toxicity. [ 14 ] Light‐based antibacterial approaches possess the potential to kill a wide range of bacteria with high spatial and temporal precision, irrespective of bacterial drug resistance status. [ 15 ] Photothermal therapy (PTT) offers thermal inactivation of bacteria; however, the elevated temperature (over 50 °C) may damage the surrounding healthy tissues and even produce heat shock proteins to generate resistance to PTT.…”
Section: Introductionmentioning
confidence: 99%